Factors Affecting Bisphosphonate Therapy Compliance In Patients With Osteogenesis Imperfecta - Yoyos Ismiarto; Firdaus Ramli F; Doddi Putra Pratama Sudjana; Naufal Chairulfatah; Wendy Yolanda Rossa (HM Publisher, 2020)
BACKGROUND: Osteogenesis imperfecta (OI) is a genetic disease with clinical manifestations in patients' bones. This study aims to investigate the factors that influence the compliance of bisphosphonate in patients with OI. METHODS: A cross-sectional analysis method was conducted and data were obtained from questionnaires answered by OI patients that received bisphosphonate. The data obtained were statistically analyzed using chi-square. RESULTS: There were 121 OI patients, age range 0-5 years (62%). Almost all patients have insurance from national health (BPJS). In this study, the average treatment compliance was 81.7%, and patients were reported to have good medication compliance of ≥80% of the treatment cycle, which was shown in 65 patients (53.7%). However, there is a relationship between parent education and treatment compliance (P = 0.046). DISCUSSION: It is a measurement of behavior related to treatment recommendations by medical professionals. On the contrary, the level of non-compliance patients with chronic disease to treatment is quite high. CONCLUSION: Good treatment compliance describes when the patient performs ≥80% of its cycle. Factors affecting it are the condition of the patient and the location of health services. Therefore, there is a relationship between compliance with the number of treatment cycles.